The roles of protocadherin-7 in colorectal cancer cells on cell proliferation and its chemoresistance - Zheng, Zhibao; Luan, Na; Tu, Kai; Liu, Feiyan; Wang, Jianwei; Sun, Jianguo (Frontiers in Pharmacology, 2023)
Despite the high mutation frequencies of KRAS, NRAS, and BRAF in colorectal cancer (CRC), there are no effective and reliable inhibitors for these biomarkers. Protocadherin7 (PCDH7) is regarded as a potentially targetable surface molecule in cancer cells and plays an important role in cancer cell proliferation, metastasis, and drug resistance of cancer cells. However, the roles and underlying mechanisms of PCDH7 in CRC remain unclear. In the current study, we found that different colorectal cancer cells expressed PCDH7 over a wide range. The levels of PCDH7 expression were positively associated with cell proliferation and drug resistance in CRC cells but negatively correlated with the potential for cell migration and invasion. Our data indicated that PCHD7 mediated the resistance of CRC cells to ABT-263 （a small molecule Bcl-2 inhibitor that induces apoptosis）by inhibiting cell apoptosis, which was supported by the downregulation of caspase3, caspase9, and PARP cleavage. We found that PCDH7 effectively promoted Mcl-1 expression at both mRNA and protein levels. Furthermore, PCDH7 activated the Wnt signaling pathway, which was confirmed by the increase in β-catenin and c-Myc expression. Finally, and notably, S63845, a novel Mcl-1 inhibitor, not only effectively attenuated the inhibitory effect of PCDH7 on cell apoptosis induced by ABT-263 in vitro, but also sensitized the PCDH7-overepressed CRC cells-derived xenografts to ABT-263 in vivo. Taken together, although PCDH7 inhibited the migration and invasion of CRC cells, it could facilitate the development of drug resistance in colorectal cancer cells by positively modulating Mcl-1 expression. The application of the Mcl-1 inhibitor S63845 could be a potential strategy for CRC chemotherapy, especially in CRC with high levels of PCDH7.